Expanding Homiletic Pedagogy Beyond Colorblindness (Homiletic, 2025)
Homiletic pedagogy in North America has recently sought to advance Diversity, Equity, and Inclusion (DEI), yet such initiatives remain entangled in colorblind frameworks that sustain Whiteness as the unmarked norm. While efforts to dismantle Whiteness have amplified Black preaching traditions, the pervasive adoption of race-neutral approaches often reinforces a narrow Black-White binary, continuing to marginalize other racialized voices, including those of Asian, Indigenous, Latine, and Middle Eastern communities. Drawing on colorblindness as a structuring vision rather than a personal attitude, this paper analyzes the 2022 and 2023 syllabus analysis reports from the Academy of Homiletics DEI Survey to reveal how faculty demographics, curricular frameworks, and evaluative practices maintain Whiteness within preaching education. Tracing how even sincere DEI initiatives may default to additive gestures and limited racial frameworks, the paper proposes theological and practical strategies for moving beyond colorblind neutrality, including naming colorblindness explicitly, reframing evaluation, and centering intersectional and global scholarship. In an era of intensified opposition to DEI, this paper reclaims homiletic pedagogy as a site for social responsibility and theological reimagination, arguing that moving beyond colorblind frameworks is essential for forming preachers who can address the layered injustices shaping congregations and the world.